Stabilization and Reform in Latin America : A Macroeconomic Perspective of the Experience Since the 1990s - Belaisch, Agnes (Occasional Papers; Occasional Paper ;, 2005)
This study examines external and domestic influences on Latin America's economic performance over the past decade and a half. It notes that over the past few years, macroeconomic policies have strengthened and structural reforms have been implemented. Together with a favorable external environment, these policies have contributed to Latin America's relatively sharp economic recovery from its last recession. The study discusses the priorities for the region's reform agenda that could help to ensure that this growing prosperity becomes entrenched. It also makes observations on the future roles of the major policymakers involved--the governments in the region; the international financial institutions, and especially the IMF; and industrial country governments.